Effect of Teachers' Instruction on Learners' Social Skills, Self-Confidence Building, Relationship Building, and Mannerism in Early Childhood Education - Shaheen, Ghazala; Ullah, Naeem; Zafar, Jam Muhammad (Annals of Human and Social Sciences, 2024)
The study intended to explore effect of teachers' instruction on learners' social skills of self-confidence building and relationship building in Early Childhood Education. The study was experimental in nature in which the quantitative method was used. The randomized pre-test and post-test control group design was applied. The study hypotheses were to investigate that there is no statistically significant effect of teachers’ instruction on learners’ social skills, there is no significant association between teachers’ instruction and learners’ social skills of self-confidence building and there is no significant association between teachers’ instruction and learners’ social skills of relationship building in early childhood education. The sample size was selected from expected population and seventy participants were chosen randomly by using a random number table from those enrolled students during the 2023 academic year. The learners’ social skills observation checklist was employed as data collection tool to examine the association between groups and statistically analyzed through non-parametric test of chi-square. The study recommends that the play-way method of instruction is more effective in developing learners' social skills as compared to traditional methods.